2012
DOI: 10.1007/s10577-012-9324-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of modified cytosines and the methylated DNA-binding protein MeCP2 with distinctive structural domains of lampbrush chromatin

Abstract: We have investigated the association of DNA methylation and proteins interpreting methylation state with the distinctive closed and open chromatin structural domains that are directly observable in the lampbrush chromosomes (LBCs) of amphibian oocytes. To establish the distribution in LBCs of MeCP2, one of the key proteins binding 5-methylcytosine-modified DNA (5mC), we expressed HA-tagged MeCP2 constructs in Xenopus laevis oocytes. Full-length MeCP2 was predominantly targeted to the closed, transcriptionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…2). These regions of lateral loops apparently correspond to the regions of lampbrush chromatin enriched with the 5-methylcytosine72 (and our unpublished data).…”
Section: Resultssupporting
confidence: 66%
“…2). These regions of lateral loops apparently correspond to the regions of lampbrush chromatin enriched with the 5-methylcytosine72 (and our unpublished data).…”
Section: Resultssupporting
confidence: 66%
“…DNA methyltransferases (DNMTs) catalyze the methylation of cytosines. Subsequent studies reveal that 5-hmC is further oxidized by TET enzymes to form 5-formylcytosine and 5-carboxylcytosine (Morgan et al, 2012). The DNMTs 3A and 3B are responsible for DNA de novo methylation in cooperation with the cofactor DNMT3L during embryogenesis, which establishes the somatic methylation pattern for the organism (Okano et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have demonstrated that the ten-eleven-translocation (TET) proteins catalyze oxidation of 5-mC into 5-hydroxymethylcytosine (5-hmC). Subsequent studies reveal that 5-hmC is further oxidized by TET enzymes to form 5-formylcytosine and 5-carboxylcytosine (Morgan et al, 2012). Imbalanced active demethylation or aberrant methylation could disturb the expression of key developmental genes, which in turn would induce cancer or tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The coding region of mouse Fabp7 was amplified by PCR and amplified cDNA was subcloned into the pcDNA ™3.1 (+) mammalian expression vector (Thermo Fisher Scientific Inc.). The sequence of nuclear localization signal peptide (NLS, CCA AAG AAG AAG CGA AAG ATG) and nuclear export signal peptide (NES, AGT CTG GCA GCT GAG TTC CGA CAC CTG CAA CTG AAG GAA) were reported previously [33,34]. Primer list to obtain amplified cDNA for Fabp7 with NLS at N or C terminus was shown in Supplemental Table 1.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%